2013
DOI: 10.1177/0885328213488228
|View full text |Cite
|
Sign up to set email alerts
|

Stent fabric fatigue of grafts supported by Z-stents versus ringed stents: An in vitro buckling test

Abstract: Stent-grafts externally fitted with a Z-shaped stents were compared to devices fitted with ringed stents in an in vitro oscillating fatigue machine at 200 cycles per minute and a pressure of 360 mmHg for scheduled durations of up to 1 week. The devices fitted with Z-stents showed a considerably lower endurance limit to buckling compared to the controls. The contact between the apexes of adjacent Z-stents resulted in significant damage to the textile scaffolds and polyester fibers due to the sharp angle of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…The importance of this undertaking is illustrated by the plethora of patents granted during the last decade . The durability of the fenestration raises some questions despite highly rewarding clinical results because the pressure of the pulsatile blood flow might further enlarge the fenestration resulting in ostial leak . Any woven fabric has a tendency to fray further to the fenestration, depending on the fabric structure and count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of this undertaking is illustrated by the plethora of patents granted during the last decade . The durability of the fenestration raises some questions despite highly rewarding clinical results because the pressure of the pulsatile blood flow might further enlarge the fenestration resulting in ostial leak . Any woven fabric has a tendency to fray further to the fenestration, depending on the fabric structure and count.…”
Section: Discussionmentioning
confidence: 99%
“…When the yarns are preserved as in this experiment, fraying of fabric can further extend. This is why we proposed the addition of a cuff to better control the ostia area . The focus of this study was solely on the fabrics.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Very rapidly, it became evident that Donghua could do much better than providing just a technological service. Joint programs were launched based upon the complementarity of these two institutions (Ji et al, 2010;Lin, Shen, Wang, & Guidoin, 2011;Liu, Wang, Lin, & Guidoin, 2012;Wang et al, 2014). Cardiovascular devices were investigated at both places: In general, biological and surgical aspects were investigated at Laval University, while materials aspects were investigated at Donghua University.…”
Section: Evolution Of the Laval University-donghua University Collabomentioning
confidence: 99%
“…We have previously shown that long-term buckling of the stent-graft can cause fabric damage at the apexes of sharp-angled Z-stents [37]. The design of such stents has been addressed in the most recent generation of stent-grafts [38,39]. …”
Section: Introductionmentioning
confidence: 99%